Corporate social responsibility and sustainable management: A study of Chinese private enterprises - Wang, Wenjie; Wang, Genxi; Asylbekovna, Bekturganova Aizhamal; Qin, Yuli (Edelweiss Applied Science and Technology, 2025)
This paper investigates the role of corporate social responsibility (CSR) in fostering sustainable management and enhancing organizational resilience among Chinese private enterprises during times of crisis. Relying on a dataset of 1,597 listed companies collected during the challenging period from January to June 2020, and incorporating detailed case studies on small and medium-sized enterprises (SMEs), the study examines how pre-crisis CSR performance influences both the stability and flexibility dimensions of resilience. Employing stakeholder theory, the resource-based view, and means-end chain theory, we develop a conceptual framework and derive empirical hypotheses. Our statistical analysis indicates that higher CSR performance prior to the COVID-19 outbreak not only mitigated financial losses but also significantly accelerated the recovery process. The paper details the estimation methods, including regression modeling and hypothesis tests with explicit formulas, and provides a thorough examination of how strong stakeholder bonds and internal resource accumulation contribute to resilience. In addition, methodological innovations such as error correction models and sensitivity analysis using alternative resilience metrics are presented. The findings underscore the notion that socially responsible behaviors, combined with strategic sustainable management practices, position Chinese private enterprises to withstand turbulent economic conditions. Implications for policymakers and enterprise managers are discussed in light of the empirical evidence and supplemented with in-depth case analyses of exemplary firms in Shandong Province.